Ética & educação ambiental : estudo da percepção ambiental da alta administração das agências de viagem do estado de Sergipe : subsídios para a responsabilidade socioambiental empresarial no parque nacional serra de Itabaiana/SE - Borja, Oscar Rodrigo Pessoa (2010)
Besides constructing an explicit environmental management instrument of good practices about the business intervention borderlines on the environment and the ethical limits that must regulate this action, this exploratory paper systematizes a scientific model which analyzes the Social Business Responsibility of the natural, social cultural and economic resources in Conservation Units at a multi-disciplined way about the managers‟ perceptions criteria of ethic, environment, responsibility and environmental education. Thus, it was intentionally done a field research using semi-structured interviews with seventeen (17) travel agencies which needed to be registered on the Brazilian Travel Agencies Association BTAA of Sergipe- SE, as well as which act or eager to act in the Pólo Serras Sergipanas, roteiro turístico Trilhas no ParNa Serra de Itabaiana. The environmental evaluation of these travel agencies high administration is positive as a speech of how to use it; however it does not work practically, since the environmental subject is not strategically placed at these travel agencies, so it has few investments on this field. It is noticeable that the environmental education which has guided behaviors, attitudes and perceptions has a neoclassic economical approach only, therefore it cannot be considered as Environmental Education, specifically spread on the basis of the sustainable and globally responsible society pact (emancipated, transforming, participative, wide, permanent, contextualized, ethic and inter-disciplined). On a ethic point of view, it was discussed the epistemological aspect of the classic tendency of the moral philosophy delving into the analytical pragmatic conception exam, detailed on the functioning of the responsibility principle: essay of an ethic for a technologic civilization, checking the hypothesis that the managers‟ ethic and moral judgments are disconnected to the universal values idea of responsibility due to the relation man/nature perspective crisis, which difficult the effectiveness of a business environmental educational pedagogical project in Conservation Units. The research intends to contribute to the responsible business ethical culture at the Travel Agencies, not only in the state of Sergipe, since the future of the sustainable societies depend on the sustainable balance of the economic, social and environmental dimensions, in a global and local responsible way. Therefore, the research believes that it can even be utopia the surpassing of the responsible human being with the generations to come. However, any disciplined and educated human being in accordance to the reality of his/her environment can be an eternal changing agent if he/she is able to do an self-critic of his/her attitudes created in relation to the world.